2006
DOI: 10.1108/02656710610648242
|View full text |Cite
|
Sign up to set email alerts
|

A study on applying FMEA to improving ERP introduction

Abstract: PurposeFacing the competition pressure of internationalization and diversification, the semiconductor industry of Taiwan has to increase the activation/utilization rate of machines, enhance flow speed and values, cut down delivery and reduce costs in an efficient way in reaction to a shortening product life cycle and the global market requirements. As a result, introduction of ERP has become a critical factor of enhancing competitiveness. The purpose of this study is establish a systematic evaluation and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Likewise, international electronic commission published an exclusive standard, which was called as IEC 812 on FMEA. Thus, unlike many techniques and tools which are developed by the researchers, FMEA was developed by the practitioners, which was recognised as a standard, for preventing failures while carrying out many operations including design and production (Yang et al, 2006;Estorilio and Posso, 2010). This development indicates a strong scientific foundation and practicality on which FMEA principles are based.…”
Section: History Of Fmeamentioning
confidence: 98%
See 2 more Smart Citations
“…Likewise, international electronic commission published an exclusive standard, which was called as IEC 812 on FMEA. Thus, unlike many techniques and tools which are developed by the researchers, FMEA was developed by the practitioners, which was recognised as a standard, for preventing failures while carrying out many operations including design and production (Yang et al, 2006;Estorilio and Posso, 2010). This development indicates a strong scientific foundation and practicality on which FMEA principles are based.…”
Section: History Of Fmeamentioning
confidence: 98%
“…Presently, adoption of FMEA has been recommended in the system standards like TS 16949 and QS -9000. Yang et al (2006) have traced the history of developing FMEA. According to these authors, Ford Company adopted FMEA from the year 1977.…”
Section: History Of Fmeamentioning
confidence: 99%
See 1 more Smart Citation
“…This framework proposed a systematic procedure for considering interdependence in the risk assessment process. Yang et al [11] suggested a systematic assessment of risks in ERP projects via the use of FMEA technique. In the developed framework, a performance matrix was built compatible with the places of the three Risk Priority Number (RPN) indicators in the performance evaluation matrix.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most common parametric approaches involving physical identification techniques with applicability have been recognized by many literatures, including the least square method, [20] the Kalman filter, [21] and the particle filter. [22] However, it is a rather challenging task to accurately and directly estimate the initialization condition and the gradient of the objective function.…”
mentioning
confidence: 99%